Outbreak of Campylobacteriosis Associated with Raccoon Contact at a Wildlife Rehabilitation Centre, Minnesota, 2013. (30th August 2016) - Saunders, S.; Smith, K.; Schott, R.; Dobbins, G.; Scheftel, J.
Summary: Campylobacteriosis is an enteric illness caused by bacteria of the genus Campylobacter . There are approximately 900 culture‐confirmed cases of campylobacteriosis reported annually to the Minnesota Department of Health (MDH). Case patients are interviewed about risk factors, including foods eaten, recreational and drinking water exposures and animal contact. In September 2013, MDH identified two Campylobacter jejuni cases who reported working at the same wildlife rehabilitation centre before illness onset. This report describes the investigation, which used a case–control study design, and identified 16 additional ill persons, for a total of 18 ill persons. Both cases and controls reported working with a variety of animals, including squirrels, chipmunks, mice, raccoons, opossums, rabbits, songbirds, waterfowl and reptiles. In univariate analyses, contact with a number of different animal species was significantly associated with illness, including raccoons (odds ratio [OR], 11.1; P < 0.001), chipmunks (OR, 3.65; P = 0.01), opossums (OR, 4.38; P = 0.005), mice (OR, 4.18; P = 0.01) and rabbits (OR, 4.36; P = 0.003). In a multivariate model, contact with raccoons was the only exposure independently associated with illness (adjusted OR, 12.2; P = 0.01). Bacterial culture and subtyping of the outbreak strain of C. jejuni from raccoon faecal samples further implicated raccoons as the source of the outbreak. Not all of the cases reported handling raccoons, suggesting that environmental contamination contributed to transmission. MDH worked with the wildlife rehabilitation centre's management to strengthen biosecurity and infection control protocols.